Targeting XPO6 inhibits prostate cancer progression and enhances the suppressive efficacy of docetaxel - Wang, Huming; Teng, Xiangyu; Lin, Yuan; Jiang, Chao; Chen, Xin; Zhang, Ying (Discover Oncology, 2023)
Although XPO6, one of the Exportin family members, functions in malignant progression of certain types of cancer, its role in prostate cancer (PCa) has not been elucidated. Herein, we investigated the oncogenic effect and clarified the downstream mechanism of XPO6 in PCa cells.